1991
DOI: 10.2135/cropsci1991.0011183x003100020035x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Emergence Force as Affected by Soil Temperature, Moisture, and Compression

Abstract: Emergence force of a seedling is a major factor influencing the ability of the seedling to emerge through a surface soil crust. This study was conducted to evaluate effects of soil physical conditions on the maximum emergence force of cotton [Gossypium hirsutum L.]. Effects of soil temperature and moisture on the emergence force were studied when the seedling was supported laterally to prevent buckling. The effect of compression of the top soil was investigated using a plate on the soil surface to simulate a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The faster rate of growth and development and the 15% higher lint yield of the cotton crop of 1998 compared with 1997 can be explained by more heat units received by the crop in 1998 (Fig. 1) Research on temperature effects on cotton growth and development has shown that rates of cotton seedling germination and emergence, rates of floral initiation, square development, and boll maturation in cotton increase with temperature up to about 32°C (Chu et al, 1991; Reddy et al, 1993; Hodges et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The faster rate of growth and development and the 15% higher lint yield of the cotton crop of 1998 compared with 1997 can be explained by more heat units received by the crop in 1998 (Fig. 1) Research on temperature effects on cotton growth and development has shown that rates of cotton seedling germination and emergence, rates of floral initiation, square development, and boll maturation in cotton increase with temperature up to about 32°C (Chu et al, 1991; Reddy et al, 1993; Hodges et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with a previous report of Arndt ( 1965) who showed that soil resistance increased in proportion to cross section area of the penetrating object. Since dicotyledonous crops push soil up with the hook for seedling emergence, thicker hypocotyl was attributed to the elongation force of seedling (Chu et al, 1991;Inouye and Jin, 1981). By contrast, gramineous crops have to penetrate the soil with their coleoptile tip.…”
Section: Discussionmentioning
confidence: 99%
“…5, al., 1965Nayyar and Josum, 1978;Matsui, 1998;Sunderman, 1964) . However, the magnitude of soil resistance to the elongating plumule might depend on the shape of the plumule, mainly the cross-section area of plumule, as indicated in reports by Chu et al ( 1991), Inouye and Jin (1981) and Arndt (1965). These investigations suggested that the tolerance of a plant to deep sowing is associated with elongation force, coleoptile length and plumule shape.…”
mentioning
confidence: 93%
“…The maximum axial growth pressure (σ max ) of shoots was measured using a method based on that of Chu et al (1991). In this approach, a shoot is allowed to grow against a balance until elongation stops and the axial growth force reaches a maximum (F max ).…”
Section: Measurement Of Shoot Growth Pressurementioning
confidence: 99%
“…Clark and Barraclough (1999) found that for a wide range of plant species, the σ max of seedling roots did not vary greatly and had a mean value of about 0.4 MPa. There are few estimates of maximum shoot growth pressure available in the literature, but Chu et al (1991) found that cotton shoots could generate 0.77 MPa at a soil water potential of −0.01 MPa.…”
Section: Effect Of Soil Strength On Emergencementioning
confidence: 99%